2021
DOI: 10.1051/e3sconf/202125007007
|View full text |Cite
|
Sign up to set email alerts
|

Development of teachers’ professional skills in education for sustainable development

Abstract: The article considers the skills and features of the personal development of a teacher in education for sustainable development (ESD). It contemplates over the influence of age differences on the formation of the professional and communicative culture of a specialist in higher education. Moreover, it describes the necessary conditions for the professional formation of the professional and communicative culture of a teacher in the development and promotion of her or him as a professional that is capable of rais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(25 reference statements)
0
0
0
Order By: Relevance
“…We will discuss how the teachers' experience with PD enabled them to enhance their classroom practices and their EfS perspectives. In the last decade, significant numbers of studies have revealed that teachers' PD needs are enormous in EfS (Pamuk et al, 2021;Sheridan et al, 2009;Tolstikova et al, 2021). It is known that teachers' knowledge and practices about a subject are highly related to their professional competencies (Neuman & Cunningham, 2009;Arrow & McLachlan, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We will discuss how the teachers' experience with PD enabled them to enhance their classroom practices and their EfS perspectives. In the last decade, significant numbers of studies have revealed that teachers' PD needs are enormous in EfS (Pamuk et al, 2021;Sheridan et al, 2009;Tolstikova et al, 2021). It is known that teachers' knowledge and practices about a subject are highly related to their professional competencies (Neuman & Cunningham, 2009;Arrow & McLachlan, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Teori Tolstikova et al (2021) menunjukkan bahwa kompetensi integrasi melibatkan kemampuan guru untuk mengaplikasikan hasil penelitian mereka dalam konteks pengajaran. Sejalan dengan teori tersebut, Martinez-Borreguero et al (2022) menyatakan bahwa menggunakan temuan penelitian untuk mendukung praktik pengajaran kritis untuk meningkatkan kualitas dan efektivitas pendidikan.…”
Section: Analisis Teori Mcginn (unclassified
“…Likewise, Calvaro (2015) shares the view that teachers needed to maximise their knowledge, and follow the advice by Delors et al (1996) that learning to learn, learning to do, learning to live, working together, and learning to be professional teachers is basic to the profession. Tolstikova et al (2021) recommend that teachers improve themselves to adapt to the 21 st century demand as traditional teaching cannot meet the requirements of LFS.…”
Section: Teacher-upgrading For Lfsmentioning
confidence: 99%